2018
DOI: 10.1155/2018/7369827
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Deformation Temperature on Microstructure Evolution and Mechanical Properties of Low‐Carbon High‐Mn Steel

Abstract: is work addresses the influence of deformation temperature in a range from −40°C to 200°C on the microstructure evolution and mechanical properties of a low-carbon high-manganese austenitic steel. e temperature range was chosen to cope at the time during sheet processing or car crash events. Experimental results show that yield stress and ultimate tensile strength gradually deteriorate with an increase in the tensile testing temperature. e dominant mechanism responsible for the strain hardening of steel change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 19 publications
3
3
0
Order By: Relevance
“…Thus, the volume fractions of the CuT component can be correlated with the densities of deformation twins. The constant high level of CuT volume fraction in the range from 25 • C to 300 • C indicates that twinning is the predominant deformation mechanism during rolling, which has also been reported by Grajcar et al [10]. The influence of this characteristic microstructure after rolling on the mechanical properties is shown in Figure 6.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Thus, the volume fractions of the CuT component can be correlated with the densities of deformation twins. The constant high level of CuT volume fraction in the range from 25 • C to 300 • C indicates that twinning is the predominant deformation mechanism during rolling, which has also been reported by Grajcar et al [10]. The influence of this characteristic microstructure after rolling on the mechanical properties is shown in Figure 6.…”
Section: Discussionsupporting
confidence: 72%
“…Above 60 mJ/m 2 the deformation mechanism changes mainly to slip [9]. This dependency in behavior on temperature and therefore the SFE of the deformation mechanisms in high manganese TWIP steels was also reported by [10][11][12]. The presented results indicate a change of the predominant deformation mechanism from mechanical twinning to dislocation glide with increasing temperature.…”
Section: Introductionsupporting
confidence: 79%
“…Grajcar et al proposed similar strengthening behavior in low C Fe-28Mn-4Si-2Al steel. They suggested that the dominant mechanism responsible for the work-hardening changes as a function of deformation temperature or strain rate, which is related to SFE [30,31].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…One of such steel grades, meeting mentioned demands and properties, are austenitic high-manganese steels [3][4][5]. These steels most often consist of 0.02% to 0.65% C, 15% to 30% Mn and Al and Si with various concentrations [6][7][8][9], in some cases also Cr or microaddtions Nb and Ti [10][11]. Gradual course of strain induced martensitic transformation [12][13][14] and/or mechanical twinning [15][16][17][18] guarantees obtaining a particularly good combination of high strength and plasticity (YS 0.2 = 250/450 MPa; UTS = 600/900 MPa; UEl = 40/80%).…”
Section: Introductionmentioning
confidence: 99%